Research participation preferences as expressed through a patient portal: implications of demographic characteristics. Issue 2 (16th August 2018) - Obeid, Jihad S; Shoaibi, Azza; Oates, Jim C; Habrat, Melissa L; Hughes-Halbert, Chanita; Lenert, Leslie A
Abstract: Objective: As patient portals are increasingly used for research recruitment, it is important to examine the demographic makeup of research registries that are populated via portals and the factors that influence participation in these registries. Methods: We examined the response to a routine research preference questionnaire among patients who were enrolled in a patient portal at an academic health center and characterized the sub-population that responded and was tracked in a research preferences registry. We examined the factors that influence choices in two research preferences: future contact for research opportunities and biobanking of de-identified specimens. Results: Out of 79 834 patients to whom the questionnaire was sent, 32% responded. Of those 74% agreed to future contact and 77% to the biobank preference. We found significantly lower odds of agreement in both preferences in minority populations, especially in the population >65 years of age when stratified by race. Individuals with higher comorbidity indexes had significantly higher odds for agreement. Discussion: The disparities in volunteerism as expressed by agreement to future contact and willingness to participate in biobanking are exacerbated by lower levels of enrollment in the patient portal by minorities, especially in the oldest age group. Future work should examine other socioeconomic factors and the differences across age groups, sicker individuals, and payer categories. Conclusion: Although patient portals can be more efficient for recruitment, researchers have to be cognizant of, and proactively address, potential biases when recruiting participants from these registries.